1993
DOI: 10.1111/j.1476-4431.1993.tb00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Thromboembolism in Dogs

Abstract: Pulmonary thromboembolism (PTE) is an infrequently diagnosed complication of many systemic diseases including heartworm disease, glomerulopathy leading to the nephrotic syndrome, immune‐mediated hemolytic anemia, hyperadrenocorticism, pancreatitis, neoplasia, and sepsis. Acute, unexplained dyspnea in a patient with minimal abnormalities on thoracic radiographs should prompt consideration of this diagnosis. Confirmation requires ventilation‐perfusion radionuclide scanning or selective pulmonary angiography. Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
2
15
0
1
Order By: Relevance
“…In this scenario, proinflammatory cytokines released in response to the bacterial infection may have activated the coagulation cascade resulting in PTE . Acute infection and associated systemic inflammation are risk factors for PTE in human and veterinary medicine . Another possibility is that the thoracotomy procedure itself could have caused enough inflammation and cellular damage that may have resulted in the development of PTE.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, proinflammatory cytokines released in response to the bacterial infection may have activated the coagulation cascade resulting in PTE . Acute infection and associated systemic inflammation are risk factors for PTE in human and veterinary medicine . Another possibility is that the thoracotomy procedure itself could have caused enough inflammation and cellular damage that may have resulted in the development of PTE.…”
Section: Discussionmentioning
confidence: 99%
“…The tests that correlated most highly with a diagnosis of DIC in humans were thrombocyte numbers, prothrombin time (PT), fibrin/fibrinogen degradation products (FDPs), and antithrombin III (AT III) levels (Bovill, 1994). In dogs, it has been suggested that platelet counts (PLT) and AT III concentrations are the most sensitive indicators of DIC (Keyes et al, 1993). The minimum laboratory data needed to evaluate haemostasis in large animals are the PLT, plasma fibrinogen content, PT (extrinsic system), activated partial thromboplastin time (APTT) (intrinsic system), FDPs and red blood cell distortion and fragmentation (produced by damage of red blood cells during passage through microvascular thrombi).…”
Section: Introductionmentioning
confidence: 99%
“…Both dogs and people receiving glucocorticoid therapy are predisposed to development of thrombotic disease . In dogs, previous studies have linked the presence of thrombotic diseases to hyperadrenocorticism or the administration of glucocorticoids . The anatomic location of these thromboemboli is variable with pulmonary arteries, aorta, and splenic vein reported most frequently .…”
Section: Introductionmentioning
confidence: 99%